Super-hydrophobic-super-oleophylic graphene oil-absorbing sponge for oil-water separation and preparation method of super-hydrophobic-super-oleophylic graphene oil-absorbing sponge
The superhydrophobic-super lipophilic graphene oil-absorbing sponge was prepared by the improved Hummers method and high-temperature reduction method, which solved the problem of complex preparation of existing materials and was unfriendly to the environment, and achieved efficient and green oil-water separation effect.
Patent Information
- Application Number
- CN202510135987.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing hydrophobic oil-absorbing materials have complex preparation processes, expensive substrate surface modification materials and uneconomical environment-friendly, which limits their application in the field of oil-water separation.
Graphene oxide (GO) was prepared by the improved Hummers method, and the reduced graphene oxide (rGO) was loaded on a melamine sponge by simple impregnation method and high-temperature reduction method, and long-chain alkanes were loaded by diesel heating to prepare a superhydrophobic-super lipophilic graphene oil-absorbing sponge.
Efficient, green and low-cost oil-water separation is achieved. The air-water contact angle of the modified sponge reaches 155.068°, the contact angle for various oils is 0°, the separation efficiency can reach more than 97%, and it has good reusability and chemical stability.
Smart Images

Figure CN119793399A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional materials and oil-water separation, and in particular to a super-hydrophobic-super-oleophilic graphene oil-absorbing sponge for oil-water separation and a preparation method thereof. Background Art
[0002] Behind the rapid economic development of today's society is a large amount of oily wastewater discharged from industrial production and daily life. At the same time, marine oil spills occur frequently. These conditions will cause serious environmental problems in the process of oil production. As people's awareness of protecting the ecological environment gradually increases, the treatment of oily wastewater and marine oil spills has become more and more urgent. Realizing oil-water separation is the most fundamental measure to solve oil pollution, protect the environment, and reduce economic waste. Traditional oil-water separation methods have the disadvantages of low separation efficiency and high operating costs. Physical adsorption is an efficient and environmentally friendly separation method. In order to overcome the limitations of traditional oil-water separation methods, selective super-wettable porous oil-absorbing materials are widely studied as potential alternatives due to their simplicity, light weight, good permeability and selective absorption capacity for oil-water mixtures. They have a large market both now and in the future. Existing hydrophobic oil-absorbing materials are limited in their application in the field of oil-water separation due to their complex preparation process, expensive substrate surface modification materials used, and unfriendly to the environment. Therefore, there is an urgent need to obtain efficient, green and low-cost oil-water separation materials and methods.
[0003] In recent years, researchers have used graphene's excellent properties of large specific surface area and strong hydrophobicity to apply it in the field of oil and organic matter adsorption, and have developed many graphene-based adsorption materials with excellent adsorption performance. Among them, the preparation of hydrophobic and oleophilic graphene-based oil-absorbing sponges is a major research direction. Porous polymer sponges are strong, elastic, high in porosity, low in density, and low in price, making them a good matrix for preparing oil-absorbing materials. However, this type of sponge is usually hydrophilic and cannot achieve oil-water separation. According to the Cassie-Baxter model, in order to give the sponge hydrophobic and oleophilic properties, the roughness of the sponge surface must be increased and the surface energy of the sponge must be reduced. At present, rGO, which is naturally hydrophobic and has good mechanical strength, is generally used to modify the sponge. The hydrophobicity of the sponge is enhanced by increasing the roughness of the sponge surface, and the sponge is treated with low surface energy substances to reduce the surface energy of the sponge. Most of the current graphene-based oil-absorbing sponges first reduce graphene oxide (GO) by solvent thermal reduction, heating reduction and chemical reduction to obtain reduced graphene oxide (rGO) and load it on the skeleton of the sponge. GO is mostly prepared by the improved Hummers method. The timeliness and safety of its preparation process need to be optimized, especially in the process of washing the graphene oxide suspension obtained by strong oxidation and exfoliation of graphene oxide from neutral to neutral and then purifying to obtain GO. At present, most of them use suction filtration or centrifugation to obtain GO slurry. These two methods are time-consuming and relatively complicated to operate. Therefore, it is necessary to optimize and improve the washing method. In addition, typical low surface energy materials include polyethylene, polypropylene, stearic acid, organosilicon and organofluorine, etc. These substances have non-polar and electrically neutral groups with low surface energy, such as alkanes, cycloalkanes and aromatics, which can be used to construct hydrophobic surfaces, but low surface energy substances are either expensive or environmentally unfriendly. Therefore, it is necessary to find a relatively cheap and environmentally friendly low surface energy material. Summary of the invention
[0004] The purpose of the present invention is to obtain a simpler method for preparing GO and an efficient, green and low-cost oil-water separation material and method, and to provide a GO and a super-hydrophobic-super-oleophilic graphene oil-absorbing sponge for oil-water separation and a preparation method thereof.
[0005] In a first aspect, the present invention provides a method for preparing a super-hydrophobic-super-oleophilic graphene oil-absorbing sponge for oil-water separation, comprising:
[0006] Step 1, weigh 4g of flake graphite, 2g of sodium nitrate, and 92mL of concentrated sulfuric acid in a beaker, place the beaker in an ice-water mixture environment and magnetically stir for 0.5h, then add 4g of potassium permanganate to the beaker every 15min, for a total of three times, and continue to react for 1h after the addition is completed, and the low-temperature reaction stage ends;
[0007] After the low temperature reaction stage, the beaker was transferred to a 35°C constant temperature water bath and stirred for 2 hours before the medium temperature reaction stage ended;
[0008] After the medium-temperature reaction stage, the temperature of the constant-temperature water bath was changed to 95°C, magnetic stirring was continued, and 200 mL of deionized water was added dropwise. After the temperature of the reaction system rose to 95°C, 400 mL of deionized water and 100 mL of hydrogen peroxide were added after 5 minutes to obtain a dispersion with a bright yellow metallic luster. After the reaction was continued for 15 minutes, the high-temperature reaction stage was terminated.
[0009] Step 2: After the high temperature reaction stage, the beaker is removed from the water bath, the obtained dispersion is ultrasonically dispersed for 30 minutes, hydrochloric acid is added and stirred for 3 minutes, and finally the obtained GO dispersion is diluted to 10L with deionized water, and the upper clear liquid is poured off by natural gravity precipitation. After repeating this step three times, the pH of the GO dispersion is neutral; the lower layer of GO slurry after the third precipitation is freeze-dried to obtain solid GO, which is shredded into fine powder and placed in a dryer for standby use;
[0010] Step three, cut the melamine sponge into cubic shapes, ultrasonically clean it with ethanol and pure water for three times, and then dry it to obtain a clean MS for use; prepare a GO dispersion with a concentration of 2.5-5.5 mg / mL, weigh GO and add it to a beaker filled with deionized water for ultrasonic dispersion for 0.5 h; immerse the original MS in the GO dispersion, take it out after ultrasonication, and dry it in an electric constant temperature blast drying oven with a drying temperature of 175°C to obtain rGO-MS; put the rGO-MS into a COD tube filled with 0# light diesel, put the COD tube into an energy-saving COD constant temperature heater and heat it at 180°C for 2-5h, and after heating, take out the pretreated rGO-MS with tweezers, squeeze out the residual diesel in the rGO-MS, and dry it in an electric constant temperature blast drying oven with a drying temperature of 180°C to obtain rGO@diesel-MS.
[0011] Furthermore, in step three, the concentration of the GO dispersion is 3-5 mg / mL.
[0012] Furthermore, in step three, the heating time is 2.5-4.5h.
[0013] In a second aspect, the present invention provides a super hydrophilic-underwater super oleophobic graphene sponge for oil-water separation prepared by the preparation method of the super hydrophilic-underwater super oleophobic graphene sponge for oil-water separation described above.
[0014] The present invention has the following beneficial effects: a super-hydrophobic-super-oleophilic graphene oil-absorbing sponge for oil-water separation of the present invention and a preparation method thereof, graphene oxide (GO) is prepared by an improved Hummers method, reduced graphene oxide (rGO) is first loaded on a melamine sponge (MS) by a simple impregnation method and a high-temperature reduction method, and then the MS is heated by diesel, and a long-chain alkane is loaded on the MS, and a super-hydrophobic-super-oleophilic graphene oil-absorbing sponge is successfully prepared. The addition of rGO can increase the roughness of the sponge surface, and the addition of long-chain alkane can reduce the surface energy of the sponge surface. The combination of the two makes the contact angle of water in the air of the modified sponge reach 155.068°, and the contact angles of various oils (organic solvents) in the air are all 0°, and it has super-hydrophobic-super-oleophilic properties. The modified MS has good elastic properties, good thermal stability and oil absorption capacity. The oil-water separation performance test shows that the separation efficiency of various oil-water mixtures can reach more than 97%. When the pump provides dynamic external force, static continuous oil-water separation without stirring and dynamic continuous oil-water separation under stirring can be achieved. The modified MS has good reusability and chemical stability. After 20 uses, the separation efficiency of various oil-water mixtures can reach more than 70%. Even in water with different pH values, oil-water separation can be achieved, and water-in-hexane emulsion can also be effectively separated. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The XRD spectra and Raman spectra of graphite, GO and rGO in Example 1; (a) is the XRD spectra of graphite and GO; (b) is the Raman spectra of graphite and GO;
[0016] Figure 2 The XRD spectra and Raman spectra of GO and rGO obtained in Example 1; (a) is the XRD spectra of GO and rGO; (b) is the Raman spectra of GO and rGO;
[0017] Figure 3 SEM characterization images of blank MS, rGO-MS, diesel-MS and rGO@diesel-MS in Example 1; (a) and (b) are blank MS; (c) and (d) are rGO-MS; (e) and (f) are diesel-MS; (g) and (h) are rGO@diesel-MS;
[0018] Figure 4 The infrared spectra of graphite, GO, rGO, rGO@diesel-MS, diesel-MS, rGO-MS and MS in Example 1; (a) is the infrared spectra of graphite, GO and rGO; (b) is the infrared spectra of MS, rGO-MS, diesel-MS and rGO@diesel-MS;
[0019] Figure 5The TGA graphs of graphite, GO, rGO, rGO@diesel-MS, diesel-MS, rGO-MS and MS in Example 1; (a) is the TGA graph of graphite, GO and rGO; (b) is the TGA graph of MS, rGO-MS, diesel-MS and rGO@diesel-MS;
[0020] Figure 6 The comparative analysis diagram of the saturated mass (volume) adsorption capacity test results of the rGO@diesel-MS obtained in Example 1 for olive oil, tetrachloroethylene, rapeseed oil, chloroform, n-hexane, toluene, lubricating oil and diesel, and the comparative diagram of the saturated mass oil absorption capacity of rGO@diesel-MS for diesel, lubricating oil and rapeseed oil with the number of cyclic oil absorption times; (a) is the saturated mass (volume) oil absorption capacity of rGO@diesel-MS for different types of oil or organic solvents; (b) is the saturated mass oil absorption capacity of rGO@diesel-MS after repeated oil absorption;
[0021] Figure 7 It is a separation efficiency diagram of rGO@diesel-MS obtained in Example 1 for diesel / water, lubricating oil / water, toluene / water, n-hexane / water, chloroform / water, rapeseed oil / water, tetrachloroethylene / water and olive oil / water mixtures, and a comparison diagram of the separation efficiency of rGO@diesel-MS for diesel / water, lubricating oil / water and rapeseed oil / water mixtures as the number of separations changes; (a) is the separation efficiency of rGO@diesel-MS for different types of oil-water mixtures; (b) is the separation efficiency of rGO@diesel-MS after repeated oil-water separation. DETAILED DESCRIPTION
[0022] The following non-limiting embodiments can enable ordinary technicians in the field to understand the present invention more comprehensively, but do not limit the present invention in any way. It is necessary to point out that the following embodiments cannot be understood as limiting the scope of protection of the present invention. If technical personnel skilled in the art make some non-essential improvements and adjustments to the present invention based on the above-mentioned content of the present invention, they still fall within the scope of protection of the present invention.
[0023] It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with the embodiments. It should be noted that the following detailed descriptions are all illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those generally understood by those of ordinary skill in the art to which the present application belongs.
[0024] The present invention adopts a simple, efficient and environmentally friendly method to prepare a super-hydrophobic-super-oleophilic graphene oil-absorbing sponge for oil-water separation, that is, graphene oxide (GO) is prepared by an improved Hummers method, and reduced graphene oxide (rGO) is first loaded on a melamine sponge (MS) by a simple impregnation method and a high-temperature reduction method, and then the MS is heated by diesel, and a long-chain alkane is loaded on the MS, and a super-hydrophobic-super-oleophilic graphene oil-absorbing sponge is successfully prepared. The addition of rGO can increase the roughness of the sponge surface, and the addition of long-chain alkanes can reduce the surface energy of the sponge surface. The combination of the two makes the contact angle of water in the air of the modified sponge reach 155.068°, and the contact angles of various oils (organic solvents) in the air are all 0°, and it has super-hydrophobic-super-oleophilic properties. The modified MS has good elastic properties, good thermal stability and oil absorption capacity. The oil-water separation performance test shows that the separation efficiency of various oil-water mixtures can reach more than 97%. When the pump provides dynamic external force, static continuous oil-water separation without stirring and dynamic continuous oil-water separation under stirring can be achieved. The modified MS has good reusability and chemical stability. After 20 uses, the separation efficiency of various oil-water mixtures can reach more than 70%. Even in water with different pH values, oil-water separation can be achieved, and water-in-hexane emulsion can also be effectively separated.
[0025] The present invention also relates to a method for preparing the GO and the super-hydrophobic-super-oleophilic graphene oil-absorbing sponge, comprising the following steps:
[0026] 1. Graphene oxide (GO) was prepared using the improved Hummers method. The specific steps are as follows.
[0027] 1) Low temperature stage
[0028] Weigh 4 g of flake graphite, 2 g of sodium nitrate, and 92 mL of concentrated sulfuric acid into a beaker, place the beaker in an ice-water mixture and magnetically stir for 0.5 h, then quantitatively add 4 g of potassium permanganate into the beaker every 15 min for a total of three times. After the addition is completed, continue the reaction for 1 h before the low-temperature reaction stage ends.
[0029] 2) Medium temperature stage
[0030] After the low-temperature reaction stage, the beaker was transferred to a 35°C constant temperature water bath and stirred for 2 h before the medium-temperature reaction stage ended.
[0031] 3) High temperature stage
[0032] After the reaction in the medium temperature stage is completed, the temperature of the constant temperature water bath is changed to 95°C, magnetic stirring is continued, and 200 mL of deionized water is slowly added drop by drop. After the temperature of the reaction system rises to 95°C, wait for another 5 minutes and then slowly add 400 mL of deionized water and 100 mL of hydrogen peroxide. At this time, a dispersion with a bright yellow metallic luster is obtained. After continuing the reaction for 15 minutes, the high temperature reaction stage is completed.
[0033] 2. Washing
[0034] After the high temperature reaction stage, the beaker was removed from the water bath, the obtained dispersion was ultrasonically dispersed for 30 minutes, hydrochloric acid was added and stirred for 3 minutes, and finally the obtained GO dispersion was diluted to 10L with deionized water, and the upper clear liquid was poured off by natural gravity precipitation. After repeating this step three times, the pH of the GO dispersion was neutral. The lower GO slurry after the third precipitation was freeze-dried to obtain solid GO, which was shredded into fine powder and placed in a dryer for later use.
[0035] 3. Super hydrophobic-super oleophilic graphene oil-absorbing sponge method
[0036] The commercial melamine sponge was cut into a fixed cubic shape, ultrasonically cleaned with ethanol and pure water for 3 times, and then dried to obtain a clean MS for use. A GO dispersion with a concentration of 2.5-5.5 mg / mL was prepared, and further, the concentration of the GO dispersion was optimized to 3-5 mg / mL. A certain mass of GO was weighed and added to a beaker containing a certain volume of deionized water for ultrasonic dispersion for 0.5 h. The clean original MS was immersed in the GO dispersion, taken out after ultrasonic treatment for a certain period of time, and dried in an electric constant temperature blast drying oven at a drying temperature of 175 ° C to obtain rGO-MS. The rGO-MS was placed in a COD tube filled with 0# light diesel, and then the COD tube was placed in an energy-saving COD constant temperature heater and heated at 180 ° C for 2-5 h. Further, the heating time was optimized to 2.5-4.5 h. After heating for a certain period of time, the pretreated rGO-MS was taken out with tweezers, the residual diesel in the rGO-MS was squeezed out, and the rGO@diesel-MS was obtained after drying in an electric constant temperature blast drying oven at a drying temperature of 180°C.
[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with Examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The specific conditions not indicated in the embodiments are carried out according to conventional conditions or the conditions recommended by the manufacturer, and the reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0038] Embodiment 1:
[0039] GO was prepared by the improved Hummers method. The commercial melamine sponge was cut into a fixed cubic shape, ultrasonically cleaned with ethanol and pure water for 3 times, and then dried to obtain a clean MS for use. A GO dispersion with a concentration of 3 mg / mL was prepared. A certain mass of GO was weighed and added to a beaker containing a certain volume of deionized water for ultrasonic dispersion for 0.5 h. The clean original MS was immersed in the GO dispersion, taken out after ultrasonic treatment for a certain period of time, and dried in an electric constant temperature blast drying oven at a drying temperature of 175 ° C to obtain rGO-MS. The rGO-MS was placed in a COD tube filled with 0# light diesel, and then the COD tube was placed in an energy-saving COD constant temperature heater and heated at 180 ° C for 2.5 h. After heating for 2.5 h, the pretreated rGO-MS was taken out with tweezers, the residual diesel in the rGO-MS was squeezed out, and rGO@diesel-MS was obtained after drying in an electric constant temperature blast drying oven at a drying temperature of 180 ° C. (GO was taken to participate in the whole high-temperature drying process of the modified sponge, and finally rGO was obtained. The clean original MS was put into the COD tube filled with 0# light diesel, and then the COD tube was put into the energy-saving COD constant temperature heater and heated at 180℃ for 2.5h. After heating for 2.5h, the pretreated MS was taken out with tweezers, the diesel remaining in the MS was squeezed out, and the diesel-MS was obtained after drying in an electric constant temperature blast drying oven with a drying temperature of 180℃.)
[0040] from Figure 1-Figure 7It can be seen that: (1) The water contact angle of rGO@diesel-MS in air is 155.068°, reaching super hydrophobicity, and the contact angle for all kinds of oils is 0°. (2) The prepared GO and rGO were characterized by XRD, Raman spectroscopy, FTIR and TGA. The results showed that GO was successfully prepared by flake graphite, and the thermal stability of rGO was significantly enhanced. The rGO@diesel-MS was characterized by SEM, FTIR and TGA. The results showed that the long-chain alkanes in rGO and diesel were successfully loaded on MS, and rGO@diesel-MS can be used normally at an ambient temperature of about 300°C. (3) The compression performance test and elastic performance test showed that the elastic performance of rGO@diesel-MS is good, which ensures its mechanical durability in oil-water separation applications. (4) Adsorption performance test shows that the saturated adsorption mass of rGO@diesel-MS for four organic solvents and four oils is 53.5419-121.6509 times and 54.0851-79.0074 times of its own weight, respectively. The saturated volume oil absorption capacity for various oils and organic solvents is 64.2341mL / g sponge-86.8213mL / g sponge and 68.9128mL / g sponge-82.5872mL / g sponge, respectively. After 20 cycles of oil absorption-extrusion, the saturated mass oil absorption capacity for diesel, lubricating oil and rapeseed oil is 44.7564g / g sponge, 70.6817g / g sponge and 63.8562g / g sponge, respectively, which is 82.8%, 89.5% and 87.0% of their initial adsorption capacity, and still maintains a high oil absorption capacity. (5) The oil-water separation performance test shows that the separation efficiency of rGO@diesel-MS for diesel / water, lubricating oil / water, toluene / water, n-hexane / water, chloroform / water, rapeseed oil / water, tetrachloroethylene / water and olive oil / water mixtures is as high as 99.57%, 97.2%, 98.7%, 99.48%, 99.22%, 98.52%, 99.73% and 99.72%, respectively. After 20 cycles of oil-water separation, the separation efficiency of rGO@diesel-MS for diesel / water, lubricating oil / water and rapeseed oil / water mixtures is 75.96%, 72.68% and 71.93%, respectively.
[0041] Embodiment 2:
[0042] GO was prepared by the improved Hummers method. The commercial melamine sponge was cut into a fixed cubic shape, ultrasonically cleaned with ethanol and pure water for 3 times, and then dried to obtain a clean MS for use. A GO dispersion with a concentration of 3.5 mg / mL was prepared. A certain mass of GO was weighed and added to a beaker containing a certain volume of deionized water for ultrasonic dispersion for 0.5 h. The clean original MS was immersed in the GO dispersion, taken out after ultrasonic treatment for a certain period of time, and dried in an electric constant temperature blast drying oven at a drying temperature of 175 ° C to obtain rGO-MS. The rGO-MS was placed in a COD tube filled with 0# light diesel, and then the COD tube was placed in an energy-saving COD constant temperature heater and heated at 180 ° C for 3 h. After heating for 3 h, the pretreated rGO-MS was taken out with tweezers, the residual diesel in the rGO-MS was squeezed out, and rGO@diesel-MS was obtained after drying in an electric constant temperature blast drying oven at a drying temperature of 180 ° C.
[0043] rGO@diesel-MS can continuously separate oil and water when used with external force provided by a pump.
[0044] Embodiment 3:
[0045] GO was prepared by the improved Hummers method. The commercial melamine sponge was cut into a fixed cubic shape, ultrasonically cleaned with ethanol and pure water for 3 times, and then dried to obtain a clean MS for use. A GO dispersion with a concentration of 4 mg / mL was prepared. A certain mass of GO was weighed and added to a beaker containing a certain volume of deionized water for ultrasonic dispersion for 0.5 h. The clean original MS was immersed in the GO dispersion, taken out after ultrasonic treatment for a certain period of time, and dried in an electric constant temperature blast drying oven at a drying temperature of 175 ° C to obtain rGO-MS. The rGO-MS was placed in a COD tube filled with 0# light diesel, and then the COD tube was placed in an energy-saving COD constant temperature heater and heated at 180 ° C for 3.5 h. After heating for 3.5 h, the pretreated rGO-MS was taken out with tweezers, the residual diesel in the rGO-MS was squeezed out, and rGO@diesel-MS was obtained after drying in an electric constant temperature blast drying oven at a drying temperature of 180 ° C.
[0046] Under the dynamic condition of severe stirring of oil-water mixture, rGO@diesel-MS can still maintain good continuous oil-water separation performance.
[0047] Embodiment 4:
[0048] GO was prepared by the improved Hummers method. The commercial melamine sponge was cut into a fixed cubic shape, ultrasonically cleaned with ethanol and pure water for 3 times, and then dried to obtain a clean MS for use. A GO dispersion with a concentration of 4.5 mg / mL was prepared. A certain mass of GO was weighed and added to a beaker containing a certain volume of deionized water for ultrasonic dispersion for 0.5 h. The clean original MS was immersed in the GO dispersion, taken out after ultrasonic treatment for a certain period of time, and dried in an electric constant temperature blast drying oven at a drying temperature of 175 ° C to obtain rGO-MS. The rGO-MS was placed in a COD tube filled with 0# light diesel, and then the COD tube was placed in an energy-saving COD constant temperature heater and heated at 180 ° C for 4 h. After heating for 4 h, the pretreated rGO-MS was taken out with tweezers, the residual diesel in the rGO-MS was squeezed out, and rGO@diesel-MS was obtained after drying in an electric constant temperature blast drying oven at a drying temperature of 180 ° C.
[0049] The oil-water emulsion separation performance test shows that rGO@diesel-MS can effectively separate toluene in water emulsion (the volume ratio of toluene and water is 1:50).
[0050] Embodiment 5:
[0051] GO was prepared by the improved Hummers method. The commercial melamine sponge was cut into a fixed cubic shape, ultrasonically cleaned with ethanol and pure water for 3 times, and then dried to obtain a clean MS for use. A GO dispersion with a concentration of 5 mg / mL was prepared. A certain mass of GO was weighed and added to a beaker containing a certain volume of deionized water for ultrasonic dispersion for 0.5 h. The clean original MS was immersed in the GO dispersion, taken out after ultrasonic treatment for a certain period of time, and dried in an electric constant temperature blast drying oven at a drying temperature of 175 ° C to obtain rGO-MS. The rGO-MS was placed in a COD tube filled with 0# light diesel, and then the COD tube was placed in an energy-saving COD constant temperature heater and heated at 180 ° C for 4.5 h. After heating for 4 h, the pretreated rGO-MS was taken out with tweezers, the residual diesel in the rGO-MS was squeezed out, and rGO@diesel-MS was obtained after drying in an electric constant temperature blast drying oven at a drying temperature of 180 ° C.
[0052] Chemical stability tests show that the modified MS can achieve oil-water separation even in water with different pH values, ensuring its use in various chemical environments.
[0053] The characterization of the prepared GO and the structural characterization and performance testing methods of the modified sponge samples in this application include:
[0054] (1) The dried sample powder was ground and pressed into tablets using the KBr tableting method. The mass ratio of the sample to KBr was 1:100. The sample was analyzed using FTIR.
[0055] (2) The thermal stability of the samples was analyzed using a thermal analyzer. The samples were subjected to thermogravimetric analysis in a nitrogen atmosphere with a heating rate of 10 °C / min and a temperature range of 40 to 600 °C.
[0056] (3) Use a desktop SEM and select different magnifications to observe the surface morphology of the sample.
[0057] (4) The wettability of the sponge surface is characterized by using a contact angle meter. A certain volume of pure water droplets and oil (organic solvent) droplets are dropped into the needle, and the static contact angle of the sample surface is tested at room temperature.
[0058] (5) A fluorescence inverted microscope was used to observe the microscopic images of the water-in-n-hexane emulsion before and after separation.
[0059] (6) Adsorption performance test: The oil absorption capacity of the modified MS is an important factor affecting its oil-water separation efficiency. In order to test the maximum oil absorption capacity of rGO@diesel-MS, the rGO@diesel-MS was accurately weighed and immersed in different oils or organic solvents (toluene, n-hexane, chloroform, rapeseed oil, etc.). After full adsorption for 10 minutes, it was taken out to make it saturated with oil. The sponge was taken out with dry and clean tweezers, and after the oil droplets stopped dripping, its mass after oil absorption was weighed, and the oil absorption multiple of the modified MS was calculated using formula (1). The saturated mass oil absorption capacity calculation formula of the sponge is:
[0060] Q0=(m0-m) / m0(1)
[0061] Where: Q0—saturated mass oil absorption capacity of sponge (maximum oil absorption mass per unit mass of sponge), g / g sponge
[0062] m0—mass of the sponge after saturation with oil, g
[0063] m—mass of sponge before absorbing oil, g
[0064] Repeat the above steps 20 times for diesel, lubricating oil and rapeseed oil, and calculate their adsorption capacity according to formula (1). The saturated volume oil absorption capacity of sponge is calculated as:
[0065] Q v =(m0-m) / (ρ·m0)(2)
[0066] Where: Q v —Saturated volume oil absorption capacity of sponge (maximum oil absorption volume per unit mass of sponge), mL / g sponge
[0067] m0—mass of the sponge after saturation with water, g
[0068] m—mass of sponge before absorbing oil, g
[0069] ρ—density of oil or organic solvent, g / mL
[0070] (7) Static oil-water separation performance test: Oil-water separation efficiency is a key indicator to determine whether the modified sponge has good performance in treating oily wastewater. Weigh 5g of oil or organic solvent (toluene, n-hexane, chloroform, rapeseed oil, etc.) and mix it with 50mL of water to prepare an oil-water mixture. Put the modified MS into 8 kinds of oil-water mixtures for oil-water separation tests. Finally, the oil-water separation efficiency is calculated by weighing method. The formula for calculating the oil-water separation efficiency is:
[0071] R = [(c1-c2) / c] × 100% (3)
[0072] Where: R—oil-water separation efficiency, %
[0073] c—initial mass of oil phase, g
[0074] c1—mass of oil-water mixture before separation, g
[0075] c2—mass of oil-water mixture after separation, g
[0076] The above steps were repeated 20 times for diesel, lubricating oil and rapeseed oil, and their oil-water separation efficiency was calculated according to formula (3).
[0077] (8) Continuous oil-water separation performance test: The continuous removal of oil from the oil-water mixture using the modified MS was carried out by a pump-assisted process. Figure 2 ) The oil-water mixture was selectively separated under continuous dynamic conditions, that is, a hose with a needle at one end was inserted into the modified MS, which was immersed in a conical flask filled with a mixture of diesel or chloroform (100mL, dyed with Sudan III) and deionized water (25mL); the other end of the hose with a needle was placed in the conical flask to collect the oil; the hose was connected to a peristaltic pump, and the oil began to be sucked out through the modified MS under the power of the pump. Two different states were achieved during the experiment: 1. Static continuous oil-water separation experiment without stirring; 2. Continuous oil-water separation experiment simulating dynamic flow conditions in actual environment after adding a stirrer.
[0078] (9) Chemical stability test: The pH value of water was adjusted to 1, 4, 7, 10 and 13 with sodium hydroxide and hydrochloric acid, and then the oil-water separation experiment was carried out at different pH values. In order to observe the oil-water separation phenomenon, the diesel was dyed with Sudan III, and the dyed diesel (3 mL) was injected into the water with a pipette, and then the modified MS was placed in the water to observe the oil-water separation on the water surface.
[0079] Separation experiment: chloroform was dyed with Sudan III, and then the dyed chloroform (2 mL) was injected into the water using a pipette, and finally the modified MS was immersed in the water to perform the oil-water separation experiment in water (10) Oil-water emulsion separation experiment: rGO@diesel-MS was used to perform the oil-water separation experiment on the water-in-hexane emulsion. The water-in-hexane emulsion was prepared by vigorously stirring a mixture of 1 mL of hexane and 50 mL of water in a wall breaker (3600 r / min) for 5 min.
[0080] It should be understood that the above-mentioned test methods and test equipment are commonly used methods in the industry to evaluate the relevant properties of hydrophobic and lipophilic modified sponges. They are only a means to characterize or evaluate the technical scheme and technical effects of the present invention. Other test methods and test equipment may also be used without affecting the final results.
[0081] From the above examples, it can be seen that the present invention uses the improved Hummers method to prepare graphene oxide (GO), and successfully prepares the super-hydrophobic-super-oleophilic rGO@diesel-MS sponge by using the impregnation method and high-temperature reduction method. The contact angle of water in the air of the modified MS is 155.068°, and the contact angle for all kinds of oils is 0°.
[0082] Graphite, prepared GO and rGO were characterized by FTIR and TGA, and the modified MS was characterized by SEM, FTIR and TGA. The results showed that GO was successfully prepared from graphite, rGO was successfully prepared from GO by high-temperature reduction, and rGO and long-chain alkanes in diesel were successfully loaded on MS, which made the modified MS exhibit superhydrophobicity and superoleophilicity, and the modified MS can be used normally at an ambient temperature of about 300°C.
[0083] The saturated mass oil absorption capacity of the modified MS for the four selected organic solvents and four oils was 53.5419-121.6509 times and 54.0851-79.0074 times of its own weight, respectively. The saturated volumetric oil absorption of the sponge was closely related to the internal storage space. The saturated volumetric oil absorption capacity was 64.2341-86.8213 mL / g sponge and 68.9128-82.5872 mL / g sponge, respectively. Compared with the saturated mass oil absorption capacity, the fluctuation range was not large. After 20 cycles of oil absorption-extrusion, the saturated mass oil absorption capacity for the three selected oils was 82.8%, 89.5% and 87.0% of their initial adsorption capacity, respectively, and the oil absorption capacity was still high.
[0084] The oil-water separation performance test shows that the separation efficiency of the modified MS for the selected 8 oil / water mixtures is as high as 97.2% to 99.73%. After 20 cycles of oil-water separation, the separation efficiency of the modified MS for the selected 3 oil / water mixtures is 75.96%, 72.68% and 71.93% respectively. The modified MS can continue to separate oil and water continuously when used under the external force provided by the pump; under the dynamic condition of severe stirring of the oil-water mixture, the modified MS can still maintain a good performance of continuous oil-water separation. The chemical stability test shows that the modified MS can achieve oil-water separation even in water with different pH values, ensuring its use in various chemical environments. The modified MS can also effectively separate water-in-hexane emulsion (the volume ratio of toluene to water is 1:50).
[0085] The preparation process of the invention is simple to operate, suitable for popularization and application, has great potential in practical applications, and can be used for oil spill cleaning and water purification, etc.
[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a super-hydrophobic-super-oleophilic graphene oil-absorbing sponge for oil-water separation, characterized in that: include: Step 1, weigh 4g of flake graphite, 2g of sodium nitrate, and 92mL of concentrated sulfuric acid in a beaker, place the beaker in an ice-water mixture environment and magnetically stir for 0.5h, then add 4g of potassium permanganate to the beaker every 15min, for a total of three times, and continue to react for 1h after the addition is completed, and the low-temperature reaction stage ends; After the low temperature reaction stage, the beaker was transferred to a 35°C constant temperature water bath and stirred for 2 hours before the medium temperature reaction stage ended; After the medium-temperature reaction stage, the temperature of the constant-temperature water bath was changed to 95°C, magnetic stirring was continued, and 200 mL of deionized water was added dropwise. After the temperature of the reaction system rose to 95°C, 400 mL of deionized water and 100 mL of hydrogen peroxide were added after 5 minutes to obtain a dispersion with a bright yellow metallic luster. After the reaction was continued for 15 minutes, the high-temperature reaction stage was terminated. Step 2: After the high temperature reaction stage, the beaker is removed from the water bath, the obtained dispersion is ultrasonically dispersed for 30 minutes, hydrochloric acid is added and stirred for 3 minutes, and finally the obtained GO dispersion is diluted to 10L with deionized water, and the upper clear liquid is poured off by natural gravity precipitation. After repeating this step three times, the pH of the GO dispersion is neutral; the lower layer of GO slurry after the third precipitation is freeze-dried to obtain solid GO, which is shredded into fine powder and placed in a dryer for standby use; Step three, cut the melamine sponge into cubic shapes, ultrasonically clean it with ethanol and pure water for three times, and then dry it to obtain a clean MS for use; prepare a GO dispersion with a concentration of 2.5-5.5 mg / mL, weigh GO and add it to a beaker filled with deionized water for ultrasonic dispersion for 0.5 h; immerse the original MS in the GO dispersion, take it out after ultrasonication, and dry it in an electric constant temperature blast drying oven with a drying temperature of 175°C to obtain rGO-MS; put the rGO-MS into a COD tube filled with 0# light diesel, put the COD tube into an energy-saving COD constant temperature heater and heat it at 180°C for 2-5h, and after heating, take out the pretreated rGO-MS with tweezers, squeeze out the residual diesel in the rGO-MS, and dry it in an electric constant temperature blast drying oven with a drying temperature of 180°C to obtain rGO@diesel-MS.
2. A method for preparing a super hydrophilic-underwater super oleophobic graphene sponge for oil-water separation as claimed in claim 1, characterized in that, In step 3, the concentration of GO dispersion is 3-5 mg / mL.
3. A method for preparing a super hydrophilic-underwater super oleophobic graphene sponge for oil-water separation as claimed in claim 1, characterized in that, In step 3, the heating time is 2.5-4.5h.
4. A super hydrophilic-underwater super oleophobic graphene sponge for oil-water separation obtained by the preparation method of the super hydrophilic-underwater super oleophobic graphene sponge for oil-water separation as described in any one of claims 1 to 3.
Citation Information
Cited By
Bipolar adsorption complex, preparation method and application thereof, and method for purifying Hainanmycin sodium
CN121222393A
Preparation method and application of graphene-based super-hydrophobic oleophylic sponge
CN122325837A